The nucleotide sequences recognized by the glucocorticoid receptor in the rabbit uteroglobin gene region are located far upstream from the initiation of transcription. - Cato, A C (EMBO J, 1984)
Although the expression of the uteroglobin gene in the lung is regulated by glucocorticoids, no binding sites for the glucocorticoid receptor are found in the promoter region nor can they be observed in the coding sequences. Instead a fragment situated 2.6 kb upstream from the start of transcription of the uteroglobin gene shows a high affinity for the receptor. Deoxyribonuclease I and methylation protection studies show three contiguous binding sites located within this fragment. All three sites show homology to the glucocorticoid receptor binding sites described for other genes. Two of them encompass the hexanucleotide 5'-TGTTCT-3', and the other binding site contains the homologue hexanucleotide, 5'-AGTCCT-3', but the contacts between the receptor and the hexanucleotides are equivalent to those found in other functional regulatory elements for glucocorticoids. These elements may therefore be responsible for the glucocorticoid regulation of uteroglobin gene expression by acting over a relatively long stretch of nucleotide sequences. IMAGES: